QUALITY WORK LIFE BALANCE OF SELF-FINANCING COLLEGE TEACHERS IN PALAKKAD DISTRICT IN PERSPECTIVE OF TOILING CLASS THEORY - C T, Salma; R. , Reena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kerala’s performance in the area of higher education is widely recognized. Self-financing college have played relevant role in educational sector . Teachers from self-financing colleges faced different problems to balance their work and family life together. The schedules are busier than ever before. They should impart all types of qualities for doing their job. When they satisfied and doing, they are given a skilled society or world. According to the KM Mani Theory of the toiling class, there is a group included farmers, teachers, labours, and those belong to working class who survive not merely on labour power alone but marginal ownership of production-management, entrepreneurship and tradeable skills and they jointly ensure their rights. By the way qualified teachers of self-financing college are not getting adequate mental and financial support from the superiors of the institutions, definitely lead to job dissatisfaction. For the successful running of the self-financing college is possible only by retaining satisfied teachers. In this study an attempt to throw light on work-life stress issues of 50 self-financing college teachers in Palakkad district.